2019
DOI: 10.21037/atm.2019.12.106
|View full text |Cite
|
Sign up to set email alerts
|

Use of high flow nasal cannula for preoxygenation and apneic oxygenation during intubation

Abstract: Need for intubation in patients with acute respiratory failure remains important when respiratory condition deteriorates and places these severely hypoxemic patients at higher risks of desaturation than patients without respiratory failure (1). Between 30 to 40% of patients with acute respiratory failure will require intubation despite initial management with high flow nasal cannula (HFNC) oxygen (2-4).This figure is higher in patients initially treated with non-invasive ventilation or with standard convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Subsequently, other clinical trials expanded indications for NHF in adults to immunocompromised patients and to patients at risk for re-intubation after surgery or in the ICU [ 24 , 25 ]. However, for the present study, we reasoned that: (1) failure of NHF (i.e., intubation) is still higher than 30% and associated with high mortality rate, especially in the case of delayed timing [ 14 ]; (2) in neonates and infants, flow rates indexed per body weight are much higher than those used in the adult population (2–3 vs. 0.5–1 L/kg PBW/min) [ 26 ]; (3) Previous physiological studies showed that effects of NHF improve at higher flow rates [ 17 ]. Thus, we conceived an exploratory physiological study to assess whether use of NHF at flow rates comparable to the neonatal setting is associated with improved physiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, other clinical trials expanded indications for NHF in adults to immunocompromised patients and to patients at risk for re-intubation after surgery or in the ICU [ 24 , 25 ]. However, for the present study, we reasoned that: (1) failure of NHF (i.e., intubation) is still higher than 30% and associated with high mortality rate, especially in the case of delayed timing [ 14 ]; (2) in neonates and infants, flow rates indexed per body weight are much higher than those used in the adult population (2–3 vs. 0.5–1 L/kg PBW/min) [ 26 ]; (3) Previous physiological studies showed that effects of NHF improve at higher flow rates [ 17 ]. Thus, we conceived an exploratory physiological study to assess whether use of NHF at flow rates comparable to the neonatal setting is associated with improved physiology.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed both the physiological and clinical benefits of noninvasive support by NHF in AHRF patients [ 9 , 10 ], to the point that NHF can already be considered as the recommended first-line noninvasive approach [ 11 13 ]. However, NHF fails to avoid intubation in around 30–40% of AHRF patients and research in this field should be aimed at finding more effective strategies able to decrease failure rate [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of patients admitted to the ICU for AHRF will fail a noninvasive ventilatory strategy and, thus, require tracheal intubation [54]. In these patients, this procedure is at even greater risk of complications, mainly oxygen desaturation [55].…”
Section: Nhf and Preoxygenationmentioning
confidence: 99%
“…[5] Currently, delivering oxygen through a high flow nasal cannula (HFNC) is being increasingly used in different clinical settings, and it is supposedly beneficial in preventing hypoxemia. [6][7][8] However, HFNC is a novel respiratory strategy treatment that delivers 50-60L/ min of warm, humidified air and many centers with limited resources do not have the appropriate equipment. [6][7][8][9][10] In centers with limited resources, oxygen delivery at 6L/min via nasal cannula or a facial mask is being used as a standard preoxygenation method.…”
Section: Medium-flow Oxygenation Through Facial Mask and Nasal Cannul...mentioning
confidence: 99%
“…[6][7][8] However, HFNC is a novel respiratory strategy treatment that delivers 50-60L/ min of warm, humidified air and many centers with limited resources do not have the appropriate equipment. [6][7][8][9][10] In centers with limited resources, oxygen delivery at 6L/min via nasal cannula or a facial mask is being used as a standard preoxygenation method. Moreover, the maximum available O2 (15L/min) from anesthesia machines is not so frequently used.…”
Section: Medium-flow Oxygenation Through Facial Mask and Nasal Cannul...mentioning
confidence: 99%